Study on the behavior of multi-cell composite T-shaped concrete-filled steel tubular columns subjected to compression under biaxial eccentricity. (August 2019) - Sui, Yi; Tu, Yongqing; Guo, Quanquan; Zhang, Jinfeng; Ke, Fei
Abstract: This paper investigates the behavior of multi-cell composite T-shaped concrete-filled steel tubular (MT-CFST) columns subjected to compression under biaxial eccentricity. Nineteen specimens were tested and presented. The main variables were the position and angle of eccentric loading. The experiment showed that the main failure modes of the specimens were overall bending and local buckling. The position and angle of eccentric loading were two important factors that affected the ultimate load of MT-CFST columns. Finite element software was used to analyze MT-CFST columns subjected to compression under biaxial eccentricity. The simulated results were in good agreement with the experimental data. By modifying the relevant parameters, the effect of the strength of concrete, the thickness of steel tubes, and the section dimension on the ultimate load of specimens were investigated. Based on fiber element analysis, the N – M curves and failure surface of the specimens were obtained. According to the fiber element analysis results, a simplified formula was proposed to predict M x / M 0x – M y / M 0y curves for specimens subjected to compression under biaxial eccentricity. It can be used to check the bearing capability of MT-CFST columns subjected to compression under biaxial eccentricity. The results predicted by the simplified formula coincide with both the results of experimental testing and finite element analysis. Highlights: Nineteen MT-CFST columns subjected to compression under biaxial eccentricity were tested. FEA models were built for investigating influence factors on the ultimate load. Fiber element analysis was used to obtain N – M curves and failure surface. Simplified formula to predict M x / M 0x – M y / M 0y curves was put forward.